KONSEP PENDIDIKAN HATI AHMAD FAHMI ZAMZAM - Akhmad Syahbudin (UIN Antasari Banjarmasin, 2017)
This study belongs to library study and is also an intellectual biography study. The nature of the study is qualitative which highlights the contributions of thought in the field of Islamic education. The Islamic education approach was applied in order to identify the contribution of thinking to the character of Islamic education, especially on the material aspects. The data were obtained from Ahmad Fahmi Zamzam's work; Empat Puluh Hadis Penawar Hati, Empat Puluh Hadis Akhlak Mulia, Empat Puluh Hadis Kelebihan Ilmu dan Ulama, Empat Puluh Hadis Peristiwa Akhir Zaman, as well as his audio visual lectures or grand recitation related to the research. The Data are grouped according to the theme of Islamic education further in the analysis. Research findings: (1) Heart education is a conscious effort to cultivate the potential of the heart to achieve perfection into a healthy heart (qalbun salîm) to justify our relationship to Allah swt and fellow human beings. (2) The importance of correcting, changing, and maintaining the heart is one of the foundations for the conduct of heart education. (3) The purpose of the heart education is directed to make the students' hearts become good and right. (4) The approach that can be done in the education of the heart is to pay attention and keep the actions of all the potential of the body from acts that can make the heart becomes dirty, by exploiting the potential of the body, the potential of eye, ear, and the potential of lathîfah ar-Rabbâniyyah. (5) The method of the heart education is grouped into two parts; First, the method of the heart education with charitable deeds, such as; prayer, zakat and alms, fasting, reciting al-Qur'an, dhikr, seeking halal rizki, having social awareness, 'amar ma'rûf and nahî munkar, and ittiba'. Second, the method of the heart education with the spiritual charities, such as; repentance, khauf, zuhud, being patient, gratitude, sincerity, mahabbah, and remembering death. (6) The curriculum of the heart education must be integrated with lathîfah ar-Rabbāniyyah i.e al-Qalbu, al-'Aql, ar-Rûh, and an-Nafs. So the educational content given should be directed to meet the spiritual and emotional material needs. (7) Evaluation of the heart education can only be measured by self-protégé children whose measure is the tranquility within the students themselves and generate noble morality.